Rice Bran Ice Cream Characteristics on Various Proportions of Rice Bran Flour with Skimmed Milk and Kinds of Stabilizer - Tri Kurniawati (Universitas Muhammadiyah Sidoarjo, 2020)
This research aimed to study rice bran ice cream on treatments of proportions of rice bran flour with skim milk ( 0:100; 25:75; and 50 : 50) and three kinds of stabilizers i.e. CMC; Carageenan; and CMC : carageenan 1 :1. Ice cream was made by mixing skim milk with rice bran flour in accordance with treatments, whipped cream and water then pas- teurized at temperature 75 oC until boiled (dough 1). Dough 2. was made of fine sugar, egg yolk and stabilizers in accordance with treatments then mixed by mixer. Dough 1 and 2 then mixed in heating process at temperature 75 oC then conditioned in ambi- ent temperature. Conditioned dough then stored an hour in refrigerator and stirred by mixer in a minute before it stored in freezer for three hours as further cooling. After the first cooling, ice cream was stirred again by mixer until soft texture was obtained. Those process then repeated once an hour until ice cream desired texture was obtained. Che- mical and physical characteristics of ice cream were observed with three replications. Data obtained were descripted and analized by regression. Result of the research showed that the higher proportions of rice bran flour with skim milk the higher fat content, crude fiber, and melting rate of rice bran ice cream. Carageenan gave highest overrun, while combination of carageenan and CMC resulted in highest melting rate and viscosity of rice bran ice cream.